Viabilidad Para La Exportación De Frijol Bola Roja Desde Cabrera Cundinamarca Colombia Hacia Miami Estados Unidos De América (2025)
The purpose of this final work is to demonstrate the viability of a international business project, specifically analyzing the feasibility of export red ball beans to the Hispanic population in Miami, United States. He main focus is on the Latin American population, who constitute a large percentage of Miami's population and have a notable affinity for this product. The red ball bean is a food that not only satisfies the nutritional needs, but is also integrated into culinary traditions of this community. Therefore, this study seeks to offer an evaluation exhaustive of market opportunities, the logistics necessary for the export and marketing strategies appropriate to establish a solid presence in this specific market.